Mobbing and labor compliance: A strategic ally against hostility - Torres Cadillo, Rosa Isabel (2022)
Labor mobbing is a common practice in organizations that, unfortunately, is growing. Indeed, workplace harassment usually goes unnoticed and starts quietly, even though, when the victim is attacked, not only is the victim damaged physically and psychologically, but the organization is also affected, since its impact will be reflected in the production or liability that the situation might cause. Therefore, labor compliance is an ideal instrument that can neutralize not only any kind of harassment, but also any irregularity that may have occurred in the organization; therefore, it is imperative to implement compliance in the law.